Academic Performance as Determinant to Pass the Licensure Examination for Teachers - Garcia, Gary C. (JPAIR Institutional Research, 2013)
Guided by the institution’s vision and mission, the researcher observed the consistency of the students’ performance during and after their studies. It also determined if relationships between examinees’ academic performance and their Licensure Examination for Teachers’ (LET) rating in Professional Education and Field of Specialization are significant. The study used the descriptive design. Respondents were PRC (LET) examinees of Southern Leyte State University – San Juan from 2007-2010. Board ratings were requested from PRC, academic records were asked from the registrar. The researcher used Mean and Percentages in describing the performance, Pearson Product Moment Coefficient Correlation in determining the significant of the relationship between academic and LETrating. A total of 39 out of 58 Examinees in four consecutive years are women. Data imply that women are more dominant than men in the field of education in terms of numbers. The correlation coefficient between examinee’s academic performance and licensure examination rating is very high in the Field of Specialization subjects, weak positive correlation in the Professional Education subjects. However, correlation in examinees academic and Licensure Examination for Teachers rating in general is moderately significant. Academic performance (grade average) of examinees gives no assurance (not a determinant) on passing PRC (LET) examination.
Keywords: Education; academic performance; Licensure Examination for Teachers (LET) PRC rating